2018
DOI: 10.4236/aid.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Multifocal Leukoencephalopathy—A Case Report in an Immunocompetent Patient

Abstract: Progressive multifocal leukoencephalopathy (PML) is a demyelinating disease of the central nervous system due to the reactivation of the JC virus, which usually occurs in immunocompromised patients and is a major opportunistic infection associated with HIV infection. We report a case of a previously healthy patient who was diagnosed with PML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Our review of the literature has shown that there are only 23 reported cases of PML in immunocompetent patients [2][3][4][5][6][7][8][9][10][11]. A previous review of the literature performed by Gheuens et al yielded an additional 32 cases [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review of the literature has shown that there are only 23 reported cases of PML in immunocompetent patients [2][3][4][5][6][7][8][9][10][11]. A previous review of the literature performed by Gheuens et al yielded an additional 32 cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the reason for JCV reactivation through a thorough review of immunological studies and whole exome sequencing is especially important when faced with PML in an immunocompetent patient, as it can lend insight into the mechanism of reactivation and potential novel treatment options [ 16 ]. Finally, previous cases of PML in immunocompetent patients offered the possibility that the patient was transiently immunodeficient at some point in their health history [ 2 - 5 ]. We cannot exclude that possibility in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation